A distinct new species of riparian rock-dwelling gecko (genus: Hemidactylus) from the southern Western Ghats - Srikanthan, Achyuthan N.; Swamy, Priyanka; Mohan, Ashwini V.; Pal, Saunak (Zootaxa, 2018)
We describe a new species of rock-dwelling gecko, Hemidactylus paaragowlipaaragowli sp. nov., from the Agastyamalai Hill Range, in the southern Western Ghats. Morphological and molecular data support the distinctiveness of the species and its close relationship to other large-bodied, tuberculate Hemidactylus spp. from the H. prashadi group from India and Sri Lanka. This species belongs to a rupicolous complex and can be distinguished from other members of the group based on the following characters: 22–24 longitudinal rows of fairly regularly arranged, subtrihedral, weakly keeled, striated tubercles at midbody; 9–11 and 10–12 subdigital lamellae on the first and fourth digits, respectively, of both manus and pes; tail with transverse series of four enlarged tubercles on each tail segment; 10–12 femoral pores on each side separated by 16–18 scales without pores; 11–13 supralabials and 9–10 infralabials.